Finanční a ekonomická strategie podniku - Čevela, Stanislav (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Bakalářská práce představuje finanční a ekonomickou strategii podniku s mnohaletou tradicí. Jeden s největších výrobců rychloběžných průmyslových vrat v ČR. Finanční analýzou posoudíme úroveň současné finanční situace podniku. Moderními metodami oceníme podnik a ohodnotíme jeho výkonnost. A nastíníme návrhy na případné zlepšení jeho finanční situace a strategie a jejich uplatnění do budoucna.

Bachelor’s thesis introduces financial and economics strategy of the firm of many years' standing tradition. One of the biggest producer of high speed industrial doors in Czech republic. We make financial analysis use of assess level actual financial situation of the firm. We use modern methods to valuation of the firm and we assesmenting efficiency of the firm. And we enthrone plans to improvement financial situation and strategy of the firm and apply them to the future.
Financial and Economics Strategy of the Firm
Keywords: Finanční analýza; oceňování podniku; výkonnost podniku; finanční zdraví podniku; ekonomická přidaná hodnota(EVA); Financial Analysis; Valuation of the Firm; Efficiency of the Firm; Financial Health of the Firm; Economic Value Added(EVA)